SATU SENYAWA ASAM ORGANIK YANG DIISOLASI DARI DAUN GEDI (Abelmoschus manihot L. Medik) ASAL SULAWESI UTARA - Mamahit, Lexie P.; Soekamto, Nunuk H. (CHEMISTRY PROGRESS, 2010)
This research was aimed to isolate and identify the structure of secondary metabolities from gedi leaf. In order to achieve this research aim, an extraction of the gedi leaf tissue with methanol solvent had been carried out. These extract then was partitioned in several organic solvents such as n-hexane, chloroform and ethyl acetate. Further, the resulted partition was fractionation and purifying undergoes an appropriate method like liquid and vacuum pressure chromatography and also determining the melting points. To determine the chemical structure of the isolate, a compilation of several spectroscopic methods, such as infrared (IR), 1H and 13 C nuclear magnetic resonance (NMR), techniques (HMQC, HMBC, and COSY). Results of this research shown that one major constituent was isolated from the leaf of gedi: heptadecanoid acid.Â